STUDI LITERATUR: PENERAPAN METODE ANITA CASSIDY DALAM PERENCANAAN STRATEGIS SISTEM INFOMASI - Safarinah, Dahlia; Hanafi, Ivan (LPPM, Universitas Negeri Jakarta, 2022)
Advances in information technology make information systems / information technology have an important role for the running of an organization today causing changes in the role of the role of efficiency and effectiveness to a strategic role. Information system is an important tool to achieve organizational goals effectively. Each organization must identify information needs systematically and carry out an analysis of the mission and functions performed, who performs them, the data and supporting information needed to perform the various functions and processes needed to structure the information most usefully. With Information Systems Planning and Information Technology (IS/IT) it is hoped that it can be a guide in developing IS/IT in the future to achieve business goals